Evasion from one pursuer in a Hilbert space - Allahabi, Fateh; Ibragimov, Gafurjan I. (World Scientific Publishing, 2012)
We study a differential game of one pursuer and one evader described by infinite systems of second order ordinary differential equations. Controls of players are subjected to geometric constraints. Differential game is considered in Hilbert spaces. We proved one theorem on evasion. Moreover, we constructed explicitly a control of the evader.